Effect of inspiratory rise time on sputum movement during ventilator hyperinflation in a test lung model. Issue 2 (June 2019) - Chapman, R.L.; Shannon, H.; Koutoumanou, E.; Main, E.
Abstract: Objectives: Physiotherapists may use ventilator hyperinflation to enhance secretion clearance for intubated patients. This study investigated the effects of altering percentage inspiratory rise time (IRT) on sputum movement, ratio of peak inspiratory to expiratory flow rate (PIF:PEF ratio) and net peak expiratory flow (PEF) during ventilator hyperinflation in a test lung model. Design: Laboratory-based bench study. Interventions: Simulated sputum (two viscosities) was inserted into clean, clear tubing and connected between a ventilator and a resuscitation bag. Thirty-six ventilator hyperinflation breaths were applied for each 5% incremental increase in IRT between 0% and 20%. Main outcome measures: The primary outcome was sputum displacement (cm). Secondary outcomes included PIF:PEF ratio and net PEF. Results: Significant cephalad sputum movement of 2.42 cm (1.59 to 3.94) occurred with IRT between 5% and 20%, compared with caudad movement of 0.53 cm (0.31 to 1.53) at 0% IRT (median sputum movement difference 3.7 cm, 95% confidence interval 2.2 to 4.8, P < 0.001). Incremental increases in IRT percentage produced linear enhancements in PIF:PEF ratio and net PEF for both sputum concentrations ( P < 0.001). However, once the critical threshold for PIF:PEF ratio of 0.9 was achieved, the distance of sputum movement remained consistent for all IRT values exceeding 5%. Conclusions: Significant increases in sputum movement occurred when IRT percentage was lengthened to achieve the optimal PIF:PEF ratio, irrespective of sputum viscosity. This provides a theoretical rationale for therapists to consider this technique when treating mechanically ventilated patients. As no additional sputum movement was seen beyond the critical PIF:PEF ratio threshold, a low IRT percentage may potentially be used to achieve effective sputum movement.